The Prenatal Hormone Milieu in Autism Spectrum Disorder - Worsham, Whitney; Dalton, Susan; Bilder, Deborah A. (Frontiers in Psychiatry, 2021)
Though the etiology of autism spectrum disorder (ASD) remains largely unknown, recent findings suggest that hormone dysregulation within the prenatal environment, in conjunction with genetic factors, may alter fetal neurodevelopment. Early emphasis has been placed on the potential role of in utero exposure to androgens, particularly testosterone, to theorize ASD as the manifestation of an “extreme male brain.” The relationship between autism risk and obstetric conditions associated with inflammation and steroid dysregulation merits a much broader understanding of the in utero steroid environment and its potential influence on fetal neuroendocrine development. The exploration of hormone dysregulation in the prenatal environment and ASD development builds upon prior research publishing associations with obstetric conditions and ASD risk. The insight gained may be applied to the development of chronic adult metabolic diseases that share prenatal risk factors with ASD. Future research directions will also be discussed.